Microbiologic Response to Periodontal Therapy and Multivariable Prediction of Clinical Outcome. Issue 12 (1st December 2017) - Mombelli, Andrea; Almaghlouth, Adnan; Cionca, Norbert; Cancela, José; Courvoisier, Delphine S.; Giannopoulou, Catherine
Abstract : Background: This study assesses the microbiologic effects of a two‐phase antimicrobial periodontal therapy and tested microbiologic, clinical, and biologic markers as prognostic indicators for clinical success. Methods: Eighty patients with chronic or aggressive periodontitis received periodontal treatment supplemented with 375 mg amoxicillin plus 500 mg metronidazole, three times daily for 7 days. In group A, antibiotics were given during the first non‐surgical phase (T1); in group B, antibiotics were given during the second surgical phase (T2). Six microorganisms, group assignment, demographic and clinical variables, peak values of 15 cytokines, and nine acute‐phase proteins in serum were evaluated as potential predictors of at least one site with probing depth (PD) >4 mm and bleeding on probing (BOP) at 12 months post‐therapy. Results: T1 decreased the counts of Porphyromonas gingivalis, Tannerella forsythia, Prevotella intermedia ( Pi ), and Treponema denticola significantly more in group A than group B. Aggregatibacter actinomycetemcomitans and Parvimonas micra ( Pm ) showed a significant decrease only if the treatment was supplemented with antibiotics, i.e., T1 in group A, or T2 in group B. After T2, differences between groups were no longer significant. A multivariable model including four parameters revealed a predictive value of Pm (odds ratio [OR] = 4.38, P = 0.02) and Pi (OR = 3.44, P = 0.049) and yielded moderate accuracy for predicting the treatment outcome (area under the curve = 0.72). Host‐derived factors and treatment sequence were not significantly associated with the outcome. Conclusions: Long‐term microbiologic outcomes of periodontal therapy with adjunctive antibiotics either in T1 or T2 were similar. Detection of Pm before therapy was a predictor for persistence of sites with PD >4 mm and BOP at 12 months post‐treatment.